Separation of naphthenic acid using hydroxide based ionic liquids - Shah, S.N. (Trans Tech Publications Ltd, 2014)
Isolation of naphthenic acid from model oil using hydroxide based ionic liquid was investigated. A detailed de-acidification study at different temperatures and different ionic liquid/model oil was performed and the content of naphthenic acid before and after extraction was calculated. The ILs containing hydroxide anions has the potential to completely deacidify model oil having high TAN with extremely low ionic liquid /oil ratio. Â© 2014 Trans Tech Publications, Switzerland.